Consideration of dynamic wind effects using a modified davenport gust response factor formulation in the structural design and evaluation of self-supporting antenna towers in the Philippines - Aquino, Ronwaldo Emmanuel R.
Self-supporting towers in the Philippines, with base aspect ratios typically greater than four (4), are currently being designed with dynamic wind effects neglected (rigid design), although it is required in the 2001 National Structural Code of the Philippines (NSCP-01) that a flexible-structure gust effect factor (GEF) should be used (flexible design) for structures with such aspect ratios. Meanwhile , there are no such GEF formulations available in literature that are appropriate for antenna towers and directly compatible with the NSCP-01, as well as information on input parameters such as the dynamic properties of towers in the Philippines .The study then first establishes guidelines for the selection of a GEF formulation. From among seven (7) formulations found in literature, the gust response factor (GRF) formulation towers in ASCE's "Guidelines for Electrical Transmission Line Structural Loading" based on the original work by Davenport in 1979 is then selected, and then modified into a GEF formulation compatible with the NSCP-01. A sensitivity analysis of this Modified Davenport formulation shows that the calculated GEF value is highly dependent upon the assumed dynamic properties, mostly notably the damping ratio. The formulation is also compared with the NSCP-01 rigid structure GEF and the ANSI/TIA/EIA-2220G-2005 (Structural Standards for Steel Antenna Towers and Antenna Supporting Structures') GEF formulation, both of which are not recommended because these are not functions of the wind field characteristics and the dynamic properties of the structure, and are based on the ASCE7 ("Minimum Design Loads for Buildings and Other Structures" GEF for buildings. Data from measurements of thirty-four (34) actual trussed towers from other countries is analyzed, and estimation formulas for the natural frequency and structural damping ratio are suggested. An estimation formula for the aerodynamic damping ratio is also suggested. The estimates are generally on the conservative side, considering the variance in the available data. Using these estimates for antenna towers in the Philippines, those with typical heights from around 30 to 60 meters are estimated to have very low damping, and that the GEF and correspondingly the wind loads in the flexible design are significantly larger than the rigid structure value in a rigid design, even for natural frequencies greater than 1 Hz. A flexible design is thus recommended for all towers in the Philippines, regardless of natural frequency. A case study is finally performed on a 60-meter antenna tower, which arrives at similar conclusions in a simple, general one-degree-of-freedom analysis of trussed structures: that if all other parameters in the wind load calculation are correct, antenna towers designed using the NSCP-01 rigid structure GEF are under-designed according to the requirements of the NSCP-01, although failure in terns of yielding of steel members is not expected. The study recommends that supplementary materials to the NSCP-01 outlining a flexible design procedure for trussed towers, be provided.